2013
DOI: 10.1111/geb.12108
|View full text |Cite
|
Sign up to set email alerts
|

Can local landscape attributes explain species richness patterns at macroecological scales?

Abstract: Aim Although the influence on species richness of landscape attributes representing landscape composition and spatial configuration has been well documented at landscape scales, its effects remain little understood at macroecological scales. We aim to assess the role of landscape attributes, and their relative importance compared with climate, habitat heterogeneity and human influence (CHH) in particular, in shaping broad-scale richness patterns. Location Mainland China.Methods Species richness data for mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
(96 reference statements)
4
31
1
Order By: Relevance
“…Our results demonstrate conspicuous relationships between landscape attributes and macroscopic patterns of mammal species richness in sub‐Saharan Africa and continental China, supporting the previous hypothesis that the strength of local landscape attributes can scale up to biogeographical levels, substantially shaping macroscopic biodiversity patterns (Martins et al, ; Ramesh et al, ; Xu et al, ). Importantly, we show that their strength depends to a considerable extent on both spatial and thematic resolutions of land cover data.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results demonstrate conspicuous relationships between landscape attributes and macroscopic patterns of mammal species richness in sub‐Saharan Africa and continental China, supporting the previous hypothesis that the strength of local landscape attributes can scale up to biogeographical levels, substantially shaping macroscopic biodiversity patterns (Martins et al, ; Ramesh et al, ; Xu et al, ). Importantly, we show that their strength depends to a considerable extent on both spatial and thematic resolutions of land cover data.…”
Section: Discussionsupporting
confidence: 89%
“…This possibility can be derived from the distinction that weak effects of landscape attributes were often found in the studies based on coarse‐resolution data (e.g., 10 km in the studies by Thuiller et al, ; Triviño, Thuiller, Cabeza, Hickler, & Araújo, ), whereas strong effects were mostly reported in more recent work using newer landscape datasets with finer resolutions (e.g., c . 0.5 km by Reino et al, ; 1 km by Xu et al, ). In this sense, testing whether the resolution of land cover data is indeed responsible for these contrasting findings can help to clarify the role of landscape attributes in shaping macroecological patterns.…”
Section: Introductionmentioning
confidence: 89%
“…The unique contribution of each variable was calculated by subtracting the pseudo-R 2 of the SAR model excluding that variable from the pseudo-R 2 of the full SAR model (Morueta-Holme et al, 2013;Xu et al, 2014). We excluded the spatial signal of SAR prediction because our focus was the effects of explanatory variables rather than their joint effects with space.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians, although ectotherm vertebrates and sensitive to temperature as well, also usually require water for reproduction, and measures of energy usually best describe their richness gradients (Rodríguez et al, ). As such, studies on the broad‐scale ecology of amphibians show that landscape heterogeneity and anthropogenic attributes play a secondary role than climate and energy availability on shaping amphibian distribution (e.g., Xu et al, but see Tsianou & Kallimanis, ). Past climate variations and historical conditions have been reported that also shape distribution patterns of amphibians (Olalla‐Tárraga et al, ).…”
Section: Introductionmentioning
confidence: 99%